Immobilization of Aspergillus sp. laccase on hierarchical silica MFI zeolite with embedded macropores - Tocco, Davide; Wisser, Dorothea; Fischer, Marcus; Schwieger, Wilhelm; Salis, Andrea; Hartmann, Martin (Colloids and Surfaces B: Biointerfaces, 2023)
Laccase from Aspergillus sp. (LC) was immobilized on functionalized silica hierarchical (microporous-macroporous) MFI zeolite (ZMFI). The obtained immobilized biocatalyst (LC#ZMFI) was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (ATR-FTIR), N2 adsorption/desorption isotherms, solid-state NMR spectroscopy and thermogravimetric analysis (TGA) confirming the chemical anchoring of the enzyme to the zeolitic support. The optimal pH, kinetic parameters (KM and Vmax), specific activity, as well as both storage and operational stability of LC#ZMFI were determined. The LC#ZMFI KM and Vmax values amount to 10.3 µM and 0.74 µmol·mg−1 min−1, respectively. The dependence of specific activity on the pH for free and immobilized LC was investigated in the pH range of 2–7, The highest specific activity was obtained at pH = 3 for both free LC and LC#ZMFI. LC#ZMFI retained up to 50 % and 30 % of its original activity after storage of 21 and 30 days, respectively. Immobilization of laccase on hierarchical silica MFI zeolite allows to carry out the reaction under acidic pH values without affecting the support structure.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Enzyme activity; Enzyme immobilization; Hierarchical porous materials; Laccase; Zeolite